Biologically Active Catecholamines Covalently Bound to Glass Beads - Venter, J. Craig (Proc Natl Acad Sci U S A, 1972)
Catecholamines bound covalently to glass beads have been found to have biological activity in several systems. Experimental evidence has been found that immobilized epinephrine and isoproterenol accelerate the heart rate in dogs, chick embryo, and chick heart cells grown in culture, whereas immobilized propranolol results in a decrease in heart rate. Isoproterenol bound to glass beads has also been shown to markedly increase the level of adenosine 3′:5′-cyclic monophosphoric acid in glial cells. The effects of the immobilized catecholamines are of longer duration than when the compounds are administered in solution. The present data indicate that the compounds are exerting their action when bound to the beads. IMAGES: